Mediating Impact of Career Adaptability on the Relationship between Emotional Intelligence and Affective Commitment - Madushani, W. M. R. K.; Nishanthi, H. M. (Department of of Human Resource Management, Faculty of Commerce and Management Studies, University of Kelaniya, Sri Lanka, 2021)
The purpose of this study was to identify the mediating impact of career adaptability on emotional intelligence and affective commitment in the AB Automotive Group in Sri Lanka. The study was carried out as quantitative explanatory research. The study is cross-sectional in nature, and a standard questionnaire was used to collect primary data through a survey using the simple random sampling technique. Questionnaires were distributed to a sample of 145 executive-level employees who are currently working in the AB automotive group of companies. SPSS (Statistical Package for the Social Science) Version 23 was used to analyze primary data. The results indicated that emotional intelligence has a significant positive effect on affective commitment. In addition, career adaptability has a significant impact on the affective commitment and emotional intelligence of the executive-level employees at the AB automotive group. Furthermore, career adaptability has partially mediated the relationship between emotional intelligence and affective commitment. Therefore, it is concluded that career adaptability has a significant impact on improving the relationship between emotional intelligence and affective commitment of the employees in the automotive industry. The present study would provide direction to HR policymakers, employees, and supervisors to implement emotional intelligence more efficiently to increase employees’ affective commitment.
Keywords: Affective Commitment, Career Adaptability, Emotional Intelligence